How to design gamification? A method for engineering gamified software - Morschheuser, Benedikt; Hassan, Lobna; Werder, Karl; Hamari, Juho (Information and software technology, 2018)
•A method for engineering gamified software is presented. It was developed via:1.Systematic review of past literature and methods to identify design principles2.Interviews with 25 leading gamification industry experts3.Evaluations in a practical use case and via industry expert interviews•Evaluations indicate the method is comprehensive, highly usable, and complete. Since its inception around 2010, gamification has become one of the top technology and software trends. However, gamification has also been regarded as one of the most challenging areas of software engineering. Beyond traditional software design requirements, designing gamification requires the command of disciplines such as (motivational/behavioral) psychology, game design, and narratology, making the development of gamified software a challenge for traditional software developers. Gamification software inhabits a finely tuned niche of software engineering that seeks for both high functionality and engagement; beyond technical flawlessness, gamification has to motivate and affect users. Consequently, it has also been projected that most gamified software is doomed to fail. This paper seeks to advance the understanding of designing gamification and to provide a comprehensive method for developing gamified software. We approach the research problem via a design science research approach; firstly, by synthesizing the current body of literature on gamification design methods and by interviewing 25 gamification experts, producing a comprehensive list of design principles for developing gamified software. Secondly, and more importantly, we develop a detailed method for engineering of gamified software based on the gathered knowledge and design principles. Finally, we conduct an evaluation of the artifacts via interviews of ten gamification experts and implementation of the engineering method in a gamification project. As results of the study, we present the method and key design principles for engineering gamified software. Based on the empirical and expert evaluation, the developed method was deemed as comprehensive, implementable, complete, and useful. We deliver a comprehensive overview of gamification guidelines and shed novel insights into the nature of gamification development and design discourse. This paper takes first steps towards a comprehensive method for gamified software engineering. [Display omitted]